Integrasi-Interkoneksi Keilmuan Bimbingan Konseling Islam (BKI) dalam Perspektif Epistemologi - Ramadhan, Lukyta Putri Amanda; Irsyadunnas, Irsyadunnas (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe scientific integration-interconnection in Islamic Guidance and Counseling (BKI) from an epistemological perspective. The method used is a literature study, which involves analyzing literature such as books, journals, and relevant research to build a theoretical foundation. The results of the study show: (1) Epistemology discusses the nature of knowledge and the relationship between truth and belief, (2) Integration-interconnection combines various fields of science, including religion and science, to produce a holistic approach, (3) The integration of science and religion, especially in the Islamic context, is important to understand human life holistically. Islamic values, such as those contained in Q.S. Al-Ahqaf (26) verse 15, can be combined with Islamic Guidance and Counseling approaches, such as cognitive-behavioral therapy (CBT) and modern psychology, to effectively deal with complex problems.  In conclusion, the integration-interconnection approach in BKI provides a strong theoretical basis and practical solutions to understand and overcome problems as a whole. This study shows that this concept supports a holistic approach that combines Islamic values and modern psychology, helping to achieve life balance and individual well-being.